2023
DOI: 10.3390/nu15092077
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Olive Oil for Skin Health: Study on the Effect of Hydroxytyrosol, Tyrosol, and Oleocanthal on Human Fibroblasts

Abstract: Fibroblasts contribute to maintaining tissue integrity and homeostasis and are a key cell population in wound healing. This cell population can be stimulated by some bioactive compounds such as extra virgin olive oil (EVOO) polyphenols. The aim of this study was to determine the effects of hydroxytyrosol (htyr), tyrosol (tyr), and oleocanthal (ole) phenolic compounds present in EVOO on the proliferation, migration, cell cycle, and antigenic profile of cultured human fibroblasts. CCD-1064Sk human fibroblast cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…In this in vitro study, the viability and migration of cultured human fibroblasts and their expression of fibronectin and α-actin were significantly increased by treatment with punicalagin or ellagic acid, phenolic compounds present in pomegranate, at doses of 10 −6 or 10 −7 M. No cell cycle alterations were produced by either treatment. Similar effects have also been reported after in vitro treatment of human fibroblasts with other bioactive substances of natural origin, such as the phenolic compounds in extra virgin olive oil, where the authors demonstrated an increase in the proliferation and migration of human fibroblasts in culture after 24 h of treatment with hydroxytyrosol, tyrosol, or oleocanthal at doses similar to those used in our study [33].…”
Section: Discussionsupporting
confidence: 89%
“…In this in vitro study, the viability and migration of cultured human fibroblasts and their expression of fibronectin and α-actin were significantly increased by treatment with punicalagin or ellagic acid, phenolic compounds present in pomegranate, at doses of 10 −6 or 10 −7 M. No cell cycle alterations were produced by either treatment. Similar effects have also been reported after in vitro treatment of human fibroblasts with other bioactive substances of natural origin, such as the phenolic compounds in extra virgin olive oil, where the authors demonstrated an increase in the proliferation and migration of human fibroblasts in culture after 24 h of treatment with hydroxytyrosol, tyrosol, or oleocanthal at doses similar to those used in our study [33].…”
Section: Discussionsupporting
confidence: 89%
“…Notably, no significant alterations were observed in cell cycle distribution or DNA integrity, suggesting the safety of these compounds. These findings underscore the potential of EVOO polyphenols in promoting tissue repair and regeneration, suggesting potential applications in wound healing processes such as cell adhesion, chemotaxis, and phagocytosis [21,22].…”
mentioning
confidence: 63%
“…The BJ cells treated with OLP and OLC maintained their proliferation potential, similar to the untreated cells ( Figure S1 ). González-Acedo et al recently showed that the phenolic compounds HT and OLC significantly increased the growth capacity of human skin fibroblasts in comparison to untreated controls at certain doses [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The BJ cells treated with OLP and OLC maintained their proliferation potential, similar to the untreated cells (Figure S1). González-Acedo et al recently showed that the phenolic compounds HT and OLC significantly increased the growth capacity of human skin fibroblasts in comparison to untreated controls at certain doses [45]. As seen in Figure 5B, OLC (−8.4 kcal/mol) was predicted to have the strongest affinity for chain A of the MAO-B dimer, followed by OLP (−7.9 kcal/mol), HTA (−7.2 kcal/mol), and HT (−6.3 kcal/mol).…”
Section: Viability Of Bj Cellsmentioning
confidence: 99%